289 PGV-001: a phase 1 trial of a personalized neoantigen peptide vaccine for the treatment of malignancies in the adjuvant setting. (9th November 2020) - Marron, Thomas; Kodysh, Julia; Rubinsteyn, Alex; Finnigan, John; Blazquez, Ana; Saxena, Mansi; Meseck, Marcia; O'Donnell, Timothy; Delbeau, Daniela; Galsky, Matthew; Doroshow, Deborah; Miles, Brett; et al.
Abstract : Background: The efficacy of T cell directed immunotherapies relies on adequate priming of T cells to tumor-specific neoantigens, which some studies have augmented with synthetic neoantigen vaccines. This is the first report of a personalized genomic vaccine (PGV-001) in multiple histologies in the adjuvant setting. Methods: Tumor and germline RNA and DNA were sequenced, and neoantigen peptides were selected using our OpenVax custom computation pipeline that identifies and ranks mutant sequences by a combination of predicted MHC-I binding affinity and neoantigen abundance within tumor. Up to 10 peptides were synthesized per patient and were administered over the course of 27 weeks in combination with the poly-ICLC. Primary objectives were to determine 1) the safety and tolerability; 2) the feasibility of PGV-001 production and administration; and 3) the immunogenicity of PGV-001. Secondary objectives included immunophenotyping neoantigen-specific T cells in peripheral blood, and characterization of peripheral blood lymphoid, myeloid and humoral responses. We report here for the first time on the primary endpoints. Results: Vaccine was synthesized for 15 patients. A mean of 1619 somatic variants (range 521–5106) were detected. Our pipeline identified a mean of 67.1 neoantigens/patient (range 8–193) and 9.7 peptides/patient were synthesized (range 7–10). 13 patients received PGV-001 (11 patients received all 10 doses and 2 patients received at least 8 doses) while 2 had progressive disease before vaccine initiation. Transient grade 1 injection site reactions were seen in 31% of patients, and one patient experienced grade 1 fever. There were no other significant adverse events. Ex vivo ELISpot analysis of patient blood demonstrated significant induction of T cell responses following receipt of 10 vaccines that were not present after the 6th vaccine, supporting the need for a prolonged dosing schedule. Robust responses were seen in both CD4 and CD8 T cells by intracellular cytokine staining for TNF-a, IFN-a, and IL-2 following in vitro expansion in the presence of vaccine antigens. Additional studies are ongoing to define the most immunogenic antigens. Conclusions: A personalized neoantigen vaccine of synthetic mutant peptides and adjuvant poly-ICLC was successfully synthesized for 15 patients and administered successfully to 87% patients over the course of 27 weeks. The vaccine was well tolerated, and T cell expansion and reactivity to synthetic neoantigens confirms immunogenicity of neoantigens identified with OpenVax. Trial Registration: NCT02721043 Ethics Approval: This study was approved by the IRB of The Mount Sinai Hospital in accordance with Federal law. HSM #15-00841.